Personality Traits and Education Level in Enhancing Financial Knowledge and Behavior of Gen Z and Millennial Women - Erna Apriani; Abdul Latif; Aprilianti Aprilianti (Journal of Enterprise and Development (JED), 2025)
Purpose: This study aims to analyze the impact of personality traits and education level on financial knowledge and financial management behavior among Gen Z and Millennial women, with financial technology serving as a mediating variable.Method: The data analysis method employed in this study is associative causality using a quantitative approach, specifically Structural Equation Modeling (SEM). The sample consists of Millennial and Gen Z women actively participating in the labor force in West Java. The sampling techniques include direct observation, online questionnaires, and interviews with 400 respondents.Result: The study found that personality traits and education levels significantly influence financial knowledge. Additionally, both financial knowledge and financial technology have a significant impact on financial management behavior. Financial knowledge also significantly affects financial technology, which mediates the relationship between personality, education level, and financial management behavior.Practical Implications for Economic Growth and Development: This study highlights the financial management behavior of women, particularly Gen Z and Millennials, as a sustainable demographic bonus towards 2045. Improved financial management practices, driven by personality, education level, financial knowledge, and financial technology, can convert income into long-term savings, thereby contributing to sustainable economic growth and development.Originality/Value: This study introduces a novel perspective by focusing on samples of Gen Z and Millennial women in the West Java region and by emphasizing the role of financial technology as a mediating variable in the analysis.